Blastocystis subtypes in patients with diabetes mellitus from the Midwest region of Brazil - Melo, Gessica Baptista de (2021)
Blastocystis sp. is an enteric protist commonly found in human fecal samples. In Brazil, few studies have been developed, but none of them has explored the presence of Blastocystis in patients with diabetes mellitus. We evaluated the occurrence and molecular identification of Blastocystis sp. among patients with diabetes mellitus in the Midwest region, Goias State, Brazil. Genomic DNA was obtained from 175 fecal samples (99 from the diabetic group and 76 from the control group). PCR was performed using pan-Blastocystis primers from the SSU-rDNA gene. Microscopic examination revealed positivity of 12.1% and 7.9% for Blastocystis in diabetics and in controls, respectively. Amplification of Blastocystis DNA was observed in 34.4% (34 of 99) and 30.3% (23 of 76) from the diabetic and control groups, respectively. Phylogenetic analyses and BLAST searches revealed six subtypes among Blastocystis isolates in the diabetic group, represented by ST1 (38.2%), ST2 (11.8%), ST3 (35.3%), ST6 (2.9%), ST7 (2.9%) and ST8 (8.8%). In the control group, ST1 (21.8%), ST2 (21.8%), ST3 (43.5%), ST6 (4.4%) and ST8 (8.7%) were identified. This study is the first report regarding the occurrence and subtypes distribution of Blastocystis in patients with diabetes mellitus in Brazil. The results reinforce the potential risk of Blastocystis infection in patients with diabetes, in addition, it contributes to the understanding of the genetic diversity of this enigmatic organism.